Triplication Patterns in Disyllabic Words in Punjabi Language: A Linguistic Analysis - Riaz, Muhammad (Annals of Human and Social Sciences, 2023)
This research investigates reduplication and triplication phenomena in Punjabi within the framework of Morphological Doubling Theory (MDT). Contrary to Harrison's (1973) assertion that triplication is exclusive to monosyllabic verbs, this study aims to demonstrate that triplication extends to both monosyllabic and disyllabic words in Punjabi. Additionally, it explores the triplication of imperative verbs and meaningless particles, challenging previous assumptions. Through analysis of Punjabi triplicate compounds, this research reveals insights into the structural and semantic aspects of triplication. The methodology involves examining linguistic data to identify patterns and deviations from established norms. The findings suggest a broader scope of triplication in Punjabi than previously recognized. This study underscores the need for a comprehensive understanding of triplication phenomena in Indo-Aryan languages. Recommendations include further exploration of triplication patterns across different linguistic contexts to enrich theoretical frameworks and language documentation efforts.